Four reasons why analysis of economic policy and religion go hand-in-hand in sub-Saharan Africa - Amma Panin (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2021)
Religion is not the focus of many policy minded economists studying sub-Saharan Africa; yet, there are important overlaps. The economics of religion is a growing sub-field which provides new tools and theories to explore the ways religious beliefs and practices affect economic outcomes. This policy brief written by Amma Panin aims to convince of the importance of the overlap between religion and policy in sub-Saharan Africa by highlighting recent advances in how economists study religion, with results that touch on institutions, beliefs and governance.
Keywords: 330